The Effects of a Training Intervention on Strength, Power and Performance in Adolescent Dancers - Dowse, Rebecca Anne (Auckland University of Technology, 2015)
There is little previous research that has investigated the effects of strength training on dancers. Therefore, the main purpose of this thesis was to determine if a nine week strength training intervention could have a significant effect on strength, power, dynamic stability and dance performance. A secondary objective was to explore the relationship between these physiological components and dance performance. Eighteen female dancers trained in jazz, ballet and/or contemporary, with five or more years’ experience were recruited from local dance schools and assigned to a strength training (n = 12) or control (n = 6) group. Anthropometry (height, seated height, mass, skinfolds), subjective dancing ability, dynamic stability (eyes open (EO), eyes closed (EC)), strength (isometric mid-thigh pull) and power (vertical countermovement jump, squat jump, single leg countermovement jump) were assessed before and after the nine week intervention period. The training group significantly increased EO overall stability (p = 0.003), EO anterior-posterior stability (p = 0.003), EC overall stability (p = 0.050), strength (p = 0.001), power (p = 0.021), dancing ability (p = 0.008) and technique (p = 0.001). The control group also experienced a significant increase in strength (p = 0.006), power (p = 0.031) and relative power (p = 0.037). Post intervention the between group analysis revealed a significant difference in EO overall stability (p = 0.008), EC overall stability (p = 0.031), EC anterior-posterior stability (p = 0.021) and technical ability (p = 0.029). A significant correlation was observed between measurements of strength and dance performance (r = 0.48; p = 0.042). Several measurements of power were also significantly associated with dancing and technical ability. This study demonstrated that strength training can have a significant effect on dynamic stability indices and dancing performance, and that strength and power may be strongly associated with a dancer’s ability. The findings also suggest that incorporating strength training may enhance strength and power adaptations in this population.
Keywords: Strength; Power; Dancers; Dynamic; Stability